Pengaruh Kemampuan Rasio Keuangan Sebagai Prediktor Pertumbuhan Laba - Norita Citra Yuliarti (Jurnal Ekonomi Akuntansi dan Manajemen, 2017)
This research wants to examine the effects of Working Capital to Total Asset (WCTA), Current Liabilities To Inventory(CLI), Total Asset Turnover(TAT), Gross Profit Margin (NPM) and to profit growth of manufacture company. The sampling technique used in this research is purposive sampling, with some criteria, those are: (1) the manufacture company listed in IDX in research period and the avaliable of financial statement as the research period 2011 until 2013 ; (3) the manufactur company has not negative profit. The result of this research shows that the data has fulfill the classical asumption, such as: no multicolinearity, no autocorrelation, no heteroscedasticity and distributed normally. From the regression analysis, found that partially Working Capital to Total Asset (WCTA), Total Asset Turnover (TAT), and Net Profit Margin (NPM) variable, have a positive significant to profit growth of manufacture company, while Current Liabilities To Inventory (CLI) doesn’t have influence to profit growth of manufacture company. From the research also known that those fourth variable (WCTA, CLI, TAT, and NPM) simoultaneously have an influence to profit growth of manufacture company. The prediction percentage of those variable simoultaneously are 35,9%. Keywords: Working Capital to Total Asset (WCTA), Current Liabilities To Inventory (CLI), Total Asset Turnover (TAT), Net Profit Margin (NPM) and profit growth.